Preventive diagnosis of dairy cow lameness - Mollo Neto, Mario [UNESP]; Nääs, Irenilza de Alencar; Carvalho, Victor Ciaco de; Conceição, Antonio Henrique Queiroz (Soc Brasil Engenharia Agricola, 2014)
This research aimed to develop a Fuzzy inference based on expert system to help preventing lameness in dairy cattle. Hoof length, nutritional parameters and floor material properties (roughness) were used to build the Fuzzy inference system. The expert system architecture was defined using Unified Modelling Language (UML). Data were collected in a commercial dairy herd using two different subgroups (H-1 and H-2), in order to validate the Fuzzy inference functions. The numbers of True Positive (TP), False Positive (FP), True Negative (TN), and False Negative (FN) responses were used to build the classifier system up, after an established gold standard comparison. A Lesion Incidence Possibility (LIP) developed function indicates the chances of a cow becoming lame. The obtained lameness percentage in H-1 and H-2 was 8.40% and 1.77%, respectively. The system estimated a Lesion Incidence Possibility (LIP) of 5.00% and 2.00% in H-1 and H-2, respectively. The system simulation presented 3.40% difference from real cattle lameness data for H-1, while for H-2, it was 0.23%; indicating the system efficiency in decision-making.

Esta pesquisa teve como objetivo desenvolver um sistema especialista baseado em inferência Fuzzy para prevenir a laminite em vacas leiteiras. O comprimento do casco, parâmetros nutricionais e propriedades do piso (rugosidade) foram utilizados para construir o sistema de inferência Fuzzy. A arquitetura do sistema especialista foi definida utilizando a Unified Modeling Language (UML). Os dados foram coletados em um rebanho leiteiro comercial, usando dois diferentes subgrupos (H1 e H2), a fim de validar as funções de inferência Fuzzy. O número de respostas Verdadeiro Positivo (TP), Falso Positivo (FP), Verdadeiro Negativo (TN) e Falso Negativo (FN) foram utilizados para a construção do classificador, contra um padrão-ouro estabelecido. A função da possibilidade de incidência da lesão (LIP) desenvolvida indica a chance de a vaca apresentar laminite. A percentagem de laminite obtida em H1 foi de 8,40%, e em H2 foi de 1,77%. Os resultados alcançados estimam uma Possibilidade de incidência de lesão (LIP) de 5,00% em H1, e de 2,00% em H2. A simulação utilizando o sistema em H1 apresentou a diferença de 3,40% a partir dos dados reais de incidência de laminite, enquanto em H2 a diferença entre a simulação e os dados reais foi de 0,23%, indicando a eficiência do sistema de tomada de decisão.
Diagnóstico preventivo de laminite em bovinos de leite
Keywords: Decision-making support; Expert system; Fuzzy inference; Apoio à decisão; Sistema especialista; Inferência Fuzzy